Energy law in Malaysia - Ansari, Abdul Haseeb (Wolters Kluwer, 2018)
A general introduction covers the geography of energy resources, sources and basic principles of energy law, and the relevant governmental institutions. Then follows a detailed description of specific legislation and regulation affecting such factors as documentation, undertakings, facilities, storage, pricing, procurement and sales, transportation, transmission, distribution, and supply of each form of energy. Case law, intergovernmental cooperation agreements, and interactions with environmental, tax, and competition law are explained.